Musculoskeletal disorders in nurses from two hospitals in South Africa: a CUPID study. (19th October 2011) - Nyantumbu, Busisiwe; Kielkowski, Danuta; Rees, David
Abstract : Objectives: To compare the prevalence of musculoskeletal pain in two hospitals, the body sites affected and associated risk factors. Methods: The study was cross-sectional and conducted in two public hospitals. A modified CUPID baseline questionnaire was administered at interview to 130 nurses in hospital A and 122 nurses in hospital B. The questionnaire asked about personal details, work activities, risk factors and musculoskeletal symptoms. Descriptive statistics were used to characterise the nurses. Pearson Chi Square was used to determine association between pain and risk factors. Results: The prevalence of any pain in the past month was three times higher (71%) in hospital B than Hospital A (45%). Site specific pain in the past month was consistently higher in hospital B than hospital A with low back pain being double (48%) that of hospital A (24%). Shoulder pain was more than three times (35%) compared with that of hospital A (11%). Wrist hand pain was more than double (21%) while knee pain was double (29%) compared with 8% and 14% in hospital A respectively. The common risk factors that were associated with the pain in hospital B were job dissatisfaction and psychological distress. Conclusions: The two hospitals were found to have a high burden of musculoskeletal disorders. The differences in the two hospitals especially the consistently high prevalence of site specific pain in hospital B need further elucidation. For this reason, data will be further analysed.